Determination of cavitation zone for cavitating waterjet machining using numerical simulation - Amresh Kumar; Tufan Chandra Bera; Bijay Kumar Rout (Flow)
Recent developments of non-traditional machining techniques, like cavitating waterjet machining (CWJM), have gained attention for their simple operation and environment friendliness with zero carbon footprints. Cavitating waterjet machining leverages the erosive power of cavity bubbles combined with a waterjet to machine or modify a workpiece. For effective CWJM, proper positioning of the workpiece is crucial. The implosion of cavity bubbles generates microjets and shock waves, creating high temperatures and pressures for a few microseconds, impacting the workpiece. This study numerically and analytically investigates the cavitation phenomenon and their effects. Numerical simulation employs an implicit finite volume scheme with the Semi-Implicit Method for Pressure Linked Equations (SIMPLE) algorithm solving Reynolds-averaged Navier–Stokes equations. It also incorporates a discrete phase model (DPM) to analyse bubble distribution and size. An analytical model calculates the hydrodynamic impact load on the workpiece. The study measures hydrodynamic stress and microjet velocities from bubble implosions, using reverse engineering to assess cavitation impact on ductile materials (aluminium and chromium steel). The result reveals a linear relationship between pit deformation and hydrodynamic impact, with impacts ranging from 200 to 1000 MPa, and microjet velocities between 100 and 800 m s−1. Finally, this work accurately predicts the standoff distance and cavitation intensity in the downstream of flow domain.